PENGEMBANGAN INOVASI TEKNOLOGI NANOPARTIKEL BERBASIS PAT UNTUK MENCIPTAKAN PRODUK YANG BERDAYA SAING - Rosniyati Suwarda; M. Syamsul Maarif (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Innovation has developed nanoparticle technology in agriculture, environment,electronics, optical, and biomedical. Nanoparticle technology advancement can be achievedwith the full support of the industry, academic and government. Technological innovation isone of the main factors driving competition. Proven technological innovation plays animportant role in encouraging industrial structure changes even the creation of newindustries. With nanometer-scale particles, will produce a new type of material is super, suchas the level of violence, power delivery, and magnetic properties. Excess it will producequality products, which is not easy to wear, because the energy-saving heat-resistant, anddoes not require refrigeration. Thus, it will save operational and maintenance costs as wellas environmentally friendly. Changes in the functional properties of nanoparticles can be acompetitive product. Government policy, industry, research and education institutions andcommunities in Indonesia in the field of nano technology is not enough to make Indonesia asone of the important players in the technology. Starch as a raw material widely available innature and is the second largest biomass in nature makes a good substrate for thepreparation of nanoparticles.